Sexual function and chemotherapy in postmenopausal women with breast cancer - Cavalheiro José Antônio (BMC Women's Health, 2012)
Abstract Background This cross-sectional, nested cohort study assessed Female Sexual Function Index (FSFI) scores in postmenopausal women with breast cancer receiving primary chemotherapy. Methods The FSFI questionnaire was administered to 24 postmenopausal women one month after diagnosis of breast cancer (post-diagnosis group) and one month after completion of the first cycle of primary anthracyclin-based chemotherapy (post-chemotherapy group). Scores were compared to those of 24 healthy postmenopausal women seeking routine gynecological care (control group). All patients were sexually active at the time of enrollment. Mean age was 57.29 ± 11.82 years in the breast cancer group and 52.58 ± 7.19 years in the control group. Results Scores in all domains of the FSFI instrument were significantly lower in the post-diagnosis group than in controls (−41.3%, p < 0.001). A further major reduction in FSFI scores was evident on completion of one cycle of primary chemotherapy (down 46.7% from post-diagnosis scores, p < 0.003), again in all domains. Six patients (25%) ceased all sexual relations, in a significant change from baseline (p < 0.001). After one chemotherapy cycle, a further five patients ceased sexual activity, for a total of 11 (45.8%) participants – a borderline significant difference (p = 0.063). Conclusion The present study shows that female sexual function as assessed by the FSFI declines significantly at two distinct points in time: upon diagnosis of breast cancer and after administration of systemic chemotherapy.